2007
DOI: 10.1039/b711244k
|View full text |Cite
|
Sign up to set email alerts
|

Current molecular design of intelligent drugs and imaging probes targeting tumor-specific microenvironments

Abstract: To address the specific challenges of cancer therapy and diagnosis, a number of approaches have been advocated for the development of tumor-targeting antitumor drugs/prodrugs and non-invasive tumor molecular imaging probes. These intelligent drugs and probes are constructed from multi-functional molecular systems. This review focuses on the molecular design of drugs and imaging probes that target tumor-specific microenvironments such as angiogenesis and hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 127 publications
0
24
0
Order By: Relevance
“…Several researchers reported that wide varieties of bioreduction-activatable prodrugs such as tegafur (Ftorafur) [1-(2-tetrahydrofuranyl)-5-fluorouracil] derivatives [2][3][4], 1-alkylcarbamoyl-5-fluorouracils [5,6], and 5-fluoro-2-deoxyuridine (5-FdUrd) derivatives [7,8] have been developed as anticancer agents [9,10]. Bioreductive prodrugs can be activated into their radical intermediates, which are oxidized to the prodrug under aerobic conditions.…”
mentioning
confidence: 99%
“…Several researchers reported that wide varieties of bioreduction-activatable prodrugs such as tegafur (Ftorafur) [1-(2-tetrahydrofuranyl)-5-fluorouracil] derivatives [2][3][4], 1-alkylcarbamoyl-5-fluorouracils [5,6], and 5-fluoro-2-deoxyuridine (5-FdUrd) derivatives [7,8] have been developed as anticancer agents [9,10]. Bioreductive prodrugs can be activated into their radical intermediates, which are oxidized to the prodrug under aerobic conditions.…”
mentioning
confidence: 99%
“…Molecular imaging presents exciting opportunities for selective detection of specific cell populations, such as those bearing markers of disease (1, 2). Cyclooxygenase-2 (COX-2) is an attractive target for molecular imaging because it is expressed in only a few normal tissues and is greatly up-regulated in inflamed tissues as well as many premalignant and malignant tumors (3, 4).…”
mentioning
confidence: 99%
“…Anticancer agents can directly interfere with a cellular process that occurs at different rates or is differentially important in the two types of cells, or they can be preferentially delivered to the cancer cells. One property of cancer cells in solid tumors that can be used to preferentially target them instead of normal cells is their relatively hypoxic nature Tanabe et al, 2007). The poor vascularization resulting from the rapid growth of tumors means that cells within the tumor are less well oxygenated than normal cells.…”
Section: Introductionmentioning
confidence: 99%